No impact man : the adventures of a guilty liberal who attempts to save the planet, and the discoveries he makes about himself and our way of life in the process - Beavan, Colin (Farrar, Straus and Giroux, 2009)
Bill McKibben meets Bill Bryson in this seriously engaging look at one man's decision to put his money where his mouth is and go off the grid for one year--while still living in New York City--to see if it's possible to make no net impact on the environment. In other words, no trash, no toxins in the water, no elevators, no subway, no products in packaging, no air-conditioning, no television. After this mad endeavor, Beavan explains to the rest of us how we can realistically live a more "eco-effective" and by turns more content life in an age of inconvenient truths.